Mathematical-Based CFD Modelling and Simulation of Mushroom Drying in Tray Dryer - Talbachew Tadesse Nadew; Petros Demissie Tegenaw; Tsegaye Sissay Tedila (Modelling and Simulation in Engineering)
In this study, CFD simulations that incorporate the inherent coupling between the moisture content of the mushroom and hot air flow in the tray dryer were performed. Conservation principles were applied to the fundamental quantities of mass, momentum, and heat. The source terms due to the moisture evaporation, the viscous and inertial resistance, and continuous evaporative cooling were determined through experimental results. Experiments were conducted to study and select the drying kinetics model at the optimum drying conditions and moisture sorption isotherm model at 30, 40, and 50°C temperatures. The best model describing the drying kinetics of mushrooms and moisture sorption isotherm model was chosen based on the lowest RMSE values and the highest R2 value. Midilli et al.’s drying kinetics model and the modified Henderson sorption isotherm model were adopted in CFD modelling. The CFD software ANSYS Fluent was used for the 3D modelling of mushroom drying in a tray dryer. The mass and energy source term equations were added to the ANSYS Fluent software using a user-defined function (UDF). The parameter permeability of medium (α) and pressure-jump coefficient (C2) appearing in the momentum source term were directly introduced in the Fluent setup as cell zone conditions. The simulation results of the moisture removal and drying temperatures were validated against experimental data. Both results are in good agreement with the experimental data, with R2 values of 0.9906 for moisture contents and 0.926 for drying temperature. Thus, simulation can be an option to study the drying mechanisms and alleviate some drawbacks of doing experiments.